Association of MHC class II haplotypes with reduced faecal nematode egg count and IgA activity in British Texel sheep. (22nd April 2019) - Ali, Alsagher O. A.; Murphy, Lisa; Stear, Abigail; Fairlie‐Clarke, Karen; Nikbakht Brujeni, Gholamreza; Donskow‐Łysoniewska, Katarzyna; Groth, David; Buitkamp, Johannes; Stear, Michael J.
Summary: Nematode infection is one of the principal diseases suffered by sheep and the class II region of the MHC has been repeatedly associated with differences in susceptibility and resistance to infection. The aim of this study was to examine the association of MHC class II haplotypes in a flock of Texel sheep with faecal egg counts and antibody responsiveness. Two haplotypes carried the DRB1*11:01 allele which has previously been associated with reduced egg counts in Scottish Blackface and Suffolk sheep. One of the two haplotypes was associated with reduced egg counts in the Texel breed, and both haplotypes were associated with reduced IgA activity against an extract from fourth‐stage larvae. The reduced IgA activity is probably a consequence of reduced numbers of fourth‐stage larvae in sheep carrying the resistance allele. The association of specific MHC alleles with reduced egg counts, reduced worm numbers and decreased IgA activity provides a mechanism for the density‐dependent regulation of parasite growth and fecundity.